Implementasi Augmented Reality Sebagai Media Edukasi Tanaman Hias Berbasis Marked Based - Alif Syahdan; Sri Wulandari (Sekawan Institut, 2023)
Ornamental plants are plants that we often encounter in the community and in public places, such as in the yard, in the park or in the school yard. Ornamental plants are usually very popular with people, especially housewives, because ornamental plants have their own characteristics and benefits, such as the snake plant (Sansevieria) which has benefits for the environment, namely it can absorb air pollution. In society, especially housewives, it is difficult to care for ornamental plants, so that the plants they cultivate often wilt or die. Therefore, media to increase education about ornamental plants must be improved to help people who want to cultivate ornamental plants. This research uses Marked Based Augmented Reality as a learning medium for the public in introducing and caring for ornamental plants. Augmented Reality is an example of technology that can visualize an object from the virtual world to the real world with a 3D object shape in real time. In this research, the Software Development Life Cycle or Waterfall (SDLC) method was used as the research method. The Software Development Life Cycle method or Waterfall model (SDLC) has five stages, namely data collection, software analysis, software design, implementation and software testing. Based on the results of black box testing, all functions in this application have run well on every Android smartphone used. Testing with the System Usability Scale (SUS) Re-spondents also got a score of 84%, so the application was declared acceptable.